Autophagy regulates levels of tumor suppressor enzyme protein phosphatase 6. Issue 12 (26th October 2020) - Fujiwara, Nobuyuki; Shibutani, Shusaku; Sakai, Yusuke; Watanabe, Toshio; Kitabayashi, Issay; Oshima, Hiroko; Oshima, Masanobu; Hoshida, Hisashi; Akada, Rinji; Usui, Tatsuya; Ohama, Takashi; Sato, Koichi
Abstract: Protein phosphatase 6 (PP6) is an essential serine/threonine protein phosphatase that acts as an important tumor suppressor. However, increased protein levels of PP6 have been observed in some cancer types, and they correlate with poor prognosis in glioblastoma. This raises a question about how PP6 protein levels are regulated in normal and transformed cells. In this study, we show that PP6 protein levels increase in response to pharmacologic and genetic inhibition of autophagy. PP6 associates with autophagic adaptor protein p62/SQSTM1 and is degraded in a p62‐dependent manner. Accordingly, protein levels of PP6 and p62 fluctuate in concert under different physiological and pathophysiological conditions. Our data reveal that PP6 is regulated by p62‐dependent autophagy and suggest that accumulation of PP6 protein in tumor tissues is caused at least partially by deficiency in autophagy. Abstract : Protein phosphatase 6 (PP6) is an essential serine/threonine protein phosphatase that acts as an important tumor suppressor. However, increased protein levels of PP6 have been observed in some cancer types, and correlate with poor prognosis in glioblastoma. Our data reveal that PP6 is regulated by p62‐dependent autophagy and suggest that accumulation of PP6 protein in tumor tissues is caused at least partially by deficiency in autophagy.